Menahan Arus: Pandangan Aisyiyah Terhadap Polemik Wacana Poligami, Keluarga Berencana, dan Jilbab, 1970 – 1991 - Hellen Cindana (Program Studi Pendidikan Sejarah Fakultas Ilmu Sosial dan Hukum Universitas Negeri Jakarta, 2020)
This study examines the view of Aisyiyah's organization on the polemics of polygamy discourse, family planning and the hijab case that occurred in the new order. In this study illustrate how Aisyiyah as a woman's Islamic organization seeks to align New order government programs with Islamic religious teachings. In the strict control of the new Order government that makes women organizations under scrutiny make the Aisyiyah organization can not do much other than to follow the programs outlined by the Government. In realizing the mission reads: